Effects of social media brand-related content on fashion products buying behaviour – a moderated mediation model. Issue 7 (8th March 2022) - Schivinski, Bruno; Pontes, Nicolas; Czarnecka, Barbara; Mao, Wen; De Vita, Jennifer; Stavropoulos, Vasileios
Abstract : Purpose: This study aims to examine in which circumstances consumer's self-congruity moderates the indirect influence of consumer-based brand equity (mediating role) in the relationship between firm-created and user-generated social media content and intention to purchase fashion products. Design/methodology/approach: In this study, the authors carried out an online survey with social media users of fashion brands and collected data from 622 participants across two samples to investigate whether consumers' perceptions of equity of fashion brands mediate the relationship between social media brand-related communication created by both firms and users and the intention to buy the fashion brands. The indirect relationship is further moderated by self-congruity. Findings: The results indicate that brand equity mediates the relationship between social media communication and purchase intentions of fashion products, and self-congruity moderates the relationship between social media communication types and purchase intentions, such that higher/lower levels of self-congruity strengthen/weaken the impact of social media communication on purchase intentions. Originality/value: This study contributes to the business and marketing literature by exploring how social media communication, branding and fashion align with the individual's self-concept and buying behaviour.